Jan Nepomucen Kamiński and his Romantic Hamlet - Kurek, Krzysztof (Theatrum Gedanense Foundation, Gdańsk, 1998)
Chapter is devoted to the translation of "Hamlet" by Jan Nepomucen Kamiński and published in 1805 by Ignacy Ścibor-Marchocki at Minkowice in Podolia. There is no doubt that Kamiński witnessed the Bogusławski production in Lwów in April 1798. While attempting at ataging the tragedy in his theatre, however, he did not make use of the Lwów script. His translation was based on on the socalled "Schroeder third adaptation" from 1778. The choice of that particular adaptation might have been a manifestation of his creative opposition to the Bogusławski production, which stemmed from a totally different understanding of the tragedy and a different vision of the drama. The opinion is supported by Kamiński's choice of his repertoire in the year 1803-1805, i.e. from the time of his performances in Kamieniec Podolski and surrounding villages. The repertoire was clearly shaped and influenced by the newest tendencies in contemporary European theatre. It was not by coincidence that Shakespeare was included in Kamiński's repertoire of 1803-1805 along with Schiller. The literary output of the author of "The Robbers" was, at the turn of the nineteenth century, a specyfic "intermediate stage" for Polish artists in familiarizing, imitating, and finally interpreting Shakespeare plays. The Schroeder adaptation used by Kamiński met all requirements of the rigours of esthetical canons of classicism, yet still it was much closer to the original than the Bogusławski's translation. Linguistic analysis of the text shows how Kamiński gradually discarded mannieristic style of Shakespearean dialogues which had to follow the rules of rhetoric so prevailing in the nineteenth century. The crispness and even a certain "coarseness" of the style of the translation make it possible for Kamiński to extract the original idea wrought by Schroeder into the strictness of the rules of classicism. The translator brought to light the inner feelings in the Shakespeare play and got rid of the influences stemming from the interpretations of the play fashioned by classicism. In the Kamiński's translation Hamlet is a dynamic person reflecting an extremely important idea for Romantics, namely that of the changeability and vagueness of the human nature.
Keywords: William Shakespeare; Hamlet; reception of William Shakespeare's "Hamlet" in Poland in the half of the nineteenth century; motif of the Polish Hamlet in Polish dramatical works